Resilience of Poultry SMEs: Sustainable Innovation for Environmental Management in Jakarta: A Literature Review - Dewa Putu Yohanes Agata L. Sandopart (Lembaga Publikasi Ilmiah Nusantara, 2024)
This study analyzes the development of the topic of SME resilience and sustainable innovation published between 2021 and 2024. Based on an analysis of 92 registered documents, it was found that the number of publications each year has grown by 27.23% annually, reflecting rapid development in this field. The majority of the publications are scholarly articles with an average document age of 1.38 years, indicating that this topic is highly relevant and receiving significant attention in the current period. Furthermore, these documents have been well received in the academic community, with an average citation per document of 5,228. The study also reveals widespread collaboration among authors, with 307 authors involved, 34.78% of whom are international, indicating a global dimension to this research. Topics discussed include resource management, operational efficiency, and the social and environmental impacts of SMEs. Overall, the results of this study show that SME resilience and sustainable innovation are gaining significant attention in the academic community, driven by international collaboration and innovative approaches to addressing sustainability challenges in business.